Trust and Household Debt. (24th October 2016) - Jiang, Danling; Lim, Sonya S
Abstract: Using a large sample of US individuals, we show that individuals with higher levels of trust have lower likelihoods of default in household debt and higher net worth. The effect is driven by trust values inherited from cultural and family backgrounds more than by trust beliefs about others. We demonstrate a causal impact of trust on financial outcomes by extracting the component of trust correlated with early-life experiences. The effect of trust is more pronounced among females, those with lower education, lower income, lower financial literacy, and higher debt-to-income ratio. Further evidence suggests that enhancing individuals' trust, to the right amount, can improve household financial well-being.